The arena of racism - Wieviorka, Michel 1946- (Theory, culture & society, 1995)
In this important addition to the sociological literature on racism, Michel Wieviorka presents a detailed and revisionary analysis of the vocabulary of racism (prejudice, discrimination, segregation and violence), arguing that racism is not reducible to these elementary forms. He shows how the experiences of institutionalized racism in America and anti-semitism in Europe can be analysed to provide an understanding of the complex transition from race to racism. As cultural identities are more and more fragmented in our societies, as the social relations defined by industrial capitalism are in decline, so too are ideas of progress and universality. It is in this context of postmodern social and economic flux that Wieviorka puts forward a definition of racism. He demonstrates that racism has to be understood as an action related to factors fixed in the dislocation between the social and the communal. One of the key contemporary texts on racism, this book will be essential reading for students of sociology, cultural studies, race relations and political science.